Thematic Realization of Car Advertisements in Kompas Newspapers - Jasawitten Brando Purba; Tina Mariany Arifin; Amrin Saragih (LINGUISTIK TERAPAN, 2015)
Thematic realization in car advertisements is quite different from other fields. There are 11 English car advertisements chosen from 8 brands. The analysis is conducted based on the principles of Thematic Structures as proposed by Halliday (1994), Bloor and Bloor (1995), and Young (2006). The data analysis reveals that the thematic structures are Unmarked Theme (89, 77%), Marked Theme (10.23%), Simple Theme (94.32%), Multiple Theme (5.68%), Constant Theme Pattern is the dominant Theme with few Linear Theme Pattern. More Marked Themes are used by expensive price cars. Based on the findings, it can be concluded that the dominant theme of the three metafuncions is the Topical Theme with emphasis on Participant and Process which aimed at engaging the readers to read and to take action in buying the advertised products. Keywords: Advertisement; Theme; and Rheme.